COPING STRESS MAHASISWA BK UPGRIS KELAS KARYAWAN - Sukmawati, Mega Nur (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
Abstract. This study is motivated by the increasing number of universities in Indonesia offering evening classes or employee-based programs for students who work. The demands of both the workplace and academia often cause stress among students. To cope with this, they develop stress coping strategies, including problem-focused coping and emotion-focused coping. The results indicate that working students more frequently employ problem-focused coping, such as seeking social support from close individuals, and emotion-focused coping, such as self-regulation. These two strategies help them manage the stress arising from the dual burden of work and studies.Abstract.This study is motivated by the increasing number of universities in Indonesia offering evening classes or employee-based programs for students who work. The demands of both the workplace and academia often cause stress among students. To cope with this, they develop stress coping strategies, including problem-focused coping and emotion-focused coping. The results indicate that working students more frequently employ problem-focused coping, such as seeking social support from close individuals, and emotion-focused coping, such as self-regulation. These two strategies help them manage the stress arising from the dual burden of work and studies.